Evolution of cystic airspaces lung lesions on immune checkpoint inhibition in non-small cell lung cancer - Maurizio Zompatori; Andrea Ardizzoni; Giuseppe Lamberti; Francesco Gelsomino; Claudia Parisi; Stefania Salvagni; Francesca Sperandi (Journal for ImmunoTherapy of Cancer)
Non-small cell lung cancer (NSCLC) can be associated with pulmonary cystic airspaces (pCAs). pCAs are radiologically classified into four types based on whether the nodule or mass extrudes the wall of the pCAs. In most cases, response evaluation of these lesions by Response Evaluation Criteria in Solid Tumors (RECIST) V.1.1 is challenging. Based on the observation of a case of morphological evolution of pCAs associated with NSCLC in a patient receiving immune checkpoint inhibitor (ICI), we reviewed retrospectively imaging scans of 92 consecutive advanced patients with NSCLC treated at our institution. Overall, three cases of pCAs associated with NSCLC obtained a remarkable change following ICI. Of note, these changes were not always seen in the context of a clear radiological objective response. The morphological changes observed may reflect a novel pattern of response to immunotherapy agents that clinicians should be aware of. This pattern of response, not reported before, warrants further investigation and, if confirmed, we believe that it should be considered in future version of immune RECIST.